2021
DOI: 10.1088/1361-6668/ac0f53
|View full text |Cite
|
Sign up to set email alerts
|

Sharp demagnetization of closed-loop HTS coil in first cycle of external AC fields induced by unexpected dynamic resistance

Abstract: Dynamic resistance leads to the demagnetization of high-T c superconducting (HTS) permanent magnets (such as closed-loop coils and tape stacks) when exposed to AC fields. This letter reports on the systematic study of an unexpected dynamic resistance occurring in first cycle AC field, which can be induced by any weak AC field-even below the threshold value 'conventionally' defined for generating dynamic resistance. This resistance is predicted by a critical-state analytical calculation, and its physical origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…The trend of U coil (t) follows that of the dynamic resistance with lagging/delay. In our previous study, we observed that the dynamic resistance of an (INS) HTS coil during the first cycle of the applied AC field was significantly greater than that during subsequent cycles [41]. This is because the superconducting current distribution (i.e., the current density distribution along the HTS tape width) in the first cycle is qualitatively different from that in the subsequent cycles: in the first cycle, the superconductor is magnetized from its 'virgin' state by the AC field [41].…”
Section: Time Evolutions Of Central Field and Voltage Of The Ni Magnetmentioning
confidence: 93%
See 2 more Smart Citations
“…The trend of U coil (t) follows that of the dynamic resistance with lagging/delay. In our previous study, we observed that the dynamic resistance of an (INS) HTS coil during the first cycle of the applied AC field was significantly greater than that during subsequent cycles [41]. This is because the superconducting current distribution (i.e., the current density distribution along the HTS tape width) in the first cycle is qualitatively different from that in the subsequent cycles: in the first cycle, the superconductor is magnetized from its 'virgin' state by the AC field [41].…”
Section: Time Evolutions Of Central Field and Voltage Of The Ni Magnetmentioning
confidence: 93%
“…The operating DC current, I op , of the HTS coil was provided by the Lakeshore Model 625 magnet source. The transverse AC field with 50 Hz, B AC , was applied by pairs of AC magnets, as detailed in our previous work [41]. The HTS coil was located at the precise central position of these AC magnets.…”
Section: Test Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major challenges concerning the PCM is that the persistent DC current circulating in the HTS coil would decay when exposed to AC fields due to the DC resistance generated in the superconductor, as illustrated by figure 1. For insulated coils [16][17][18][19], bulks [20,21] and stacks [22,23] that carry a persistent DC current, their demagnetization behavior under external AC fields have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Also, many studies were conducted on magnetization loss in the stacked REBCO coated conductors [39,[145][146][147][148][149][150][151] , and insulated or non-insulated REBCO coils [54,56,[152][153][154][155] . N. Bykovsky et.…”
Section: (B) Measurements For Transport Lossmentioning
confidence: 99%